A new C1 4-node flat laminated shell element based on a generalized plate formulation. (June 2021) - Caliri, Mauricio F.; Ferreira, Antonio J.M.; Tita, Volnei
Abstract: The performance of an element with C1 continuity in the thickness direction was investigated within the scope of unified plate and shell formulations considering skew elements and the shear locking problem. A remedy for the shear locking pathology was found in the form of an algorithm which applies a penalty factor when the element is thinner than L E ∕ H = 2 . Moreover, the proposed test cases showed the ability of Caliri's Generalized Formulation - CGF to better control the through-the-thickness behavior of the structure at the boundary conditions. Consistent results were obtained even for skew meshes and laminated shells. Highlights: The new element did not suffer from the lack of theoretical C2 continuity. The proposed penalty factor method eliminates the shear locking problem successfully. 3D boundary conditions can be obtained by properly setting the available DOFs. Consistent results along the thickness of the laminated panels were achieved.